BALANCING FAITH AND COMMERCE: MAQASID ANALYSIS OF COFFEE SHOP OPERATING HOUR REGULATION IN ACEH - Munadiati; Kurlillah, Anis; Bahri, Eni Haryani; Zulhilmi (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2025)
Abstract In Aceh, Indonesia, Governor's Circular SE-11286 regulates coffee shop operating hours aiming to strengthen Islamic Sharia compliance. This policy sparks tension with the crucial role these businesses play in local commerce, employment, and community engagement across key hub (e.g., Langsa, Lhokseumawe) and destination (e.g., Banda Aceh) cities. This article investigates the balance between faith-based regulation and economic vitality. Employing a public policy research approach with interpretive analysis, the study evaluates SE-11286 through the Maqasid al-Shariah framework, conceptualized systemically, examining policy articulation, social construction, and socio-economic impacts. Findings indicate significant challenges in aligning the regulation with holistic Maqasid principles. The policy's focus potentially prioritizes aspects of Hifz al-Din while disproportionately compromising Hifz al-Mal negatively impacting livelihoods and the function of coffee shops as vital economic and social hubs. The study concludes that effective Sharia-informed governance requires a comprehensive Maqasid application, balancing diverse objectives and necessitating thorough socio-economic impact assessments prior to implementation. This research provides critical implications for formulating ethically grounded and economically sustainable regulations within contemporary Islamic contexts. Keyword: Maqasid al-Shariah, Public Policy, Coffee Shops, Economic Regulation, Aceh